Sistem Pendukung Keputusan Pemberian Beasiswa Menggunakan Metode Simple Additive Weighting Di Universitas Panca Marga Probolinggo - Aprilianto, Ferry Romidhoni; Sagirani, Tri; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Panca Marga Probolinggo University as a place of learning and self developments provides facilities for student achievements scholarships. The scholarship program is expected to spur student interest in learning to be more accomplished. In determining the scholarship recipients, the administrator selects candidates for faculty scholarship recipients base on existing criteria. In the process of selecting, admin faculty have difficulty selecting a data prospective recipients. Because each type of scholarship criteria and weight have different criteria. It makes the calculation of the value criteria requires precision. Knowing the problem that occur, the autors designed the decision support system and make the determination of scholarship by using the SAW method. This system can help admins to perform data administration faculty scholarship recipients, the data type of scholarship, the data criteria, criteria weighting data, and data recipients. With this system the loss of data can be minimize. After testing the use of decision support system determining the scholarship by using the SAW method, it can be concluded that this decision support system to help admins faculty in performing their duties. Keywords: Decision Supprot System, SAW and scholarship.